PENGELOLAAN ANGGARAN PADA MASA PANDEMI COVID-19 DI KPPBC TMP A MARUNDA DALAM PERSPEKTIF AKUNTANSI - Muhammad Aripradana Wibawa; Puji Wibowo (Jurnalku, 2021)
The Covid-19 pandemic has caused dynamics in the budget absorption process, sothat budget revisions are very crucial in determining the absorption rate and work unit operations. This study aims to measure the accuracy of KPPBC TMP A Marunda in preparing the budget and knowing the policies taken in the face of the Covid-19 pandemic. The analytical method used is a qualitative analysis by processing data through interviews, observations, and literature studies. Based on the results of data processing, the budget revision in the 2020 fiscal year was carried out with several themes, including budget revisions in terms of changing budget ceilings, revisions to budget shifts in terms of fixed budget ceilings, and administrative revisions by making budget savings during the Covid-19 pandemic, adding a special account for handling Covid-19 and revision of the minus ceiling. Budget revisions are carried out by paying attention to budget performance against realization and the amount of the budget ceiling. Budget revisions in the context of budget savings to deal with the Covid-19 pandemic are carried out by reducing budgets sourced from accounts that are considered not become a priority. The presentation of the special account for handling Covid-19 in the financial statements does not have a special segment, it is presented as goods expenditure in the budget realization report and presented as goods and services expense in the operational report.   Pandemi Covid-19 menyebabkan terjadinya dinamika dalam proses penyerapan anggaran, sehingga revisi anggaran menjadi hal yang sangat krusial dalam menentukan tingkat penyerapan dan operasional satuan kerja. Penelitian ini bertujuan untuk mengukur ketepatan KPPBC TMP A Marunda dalam melakukan penyusunan anggaran dan mengetahui kebijakan yang diambil dalam menghadapi pandemi Covid-19. Metode analisis yang digunakan adalah analisis kualitatif dengan melakukan pengolahan data melalui hasil wawancara, observasi dan studi literatur. Berdasarkan hasil pengolahan data, revisi anggaran pada tahun anggaran 2020 dilakukan dengan beberapa tema, diantaranya revisi anggaran dalam hal pagu anggaran berubah, revisi pergeseran anggaran dalam hal pagu anggaran tetap, dan revisi administrasi dengan melakukan penghematan anggaran selama masa pandemi Covid-19, melakukan penambahan akun khusus penanganan Covid-19 dan revisi pagu minus. Revisi anggaran dilakukan dengan memperhatikan kinerja anggaran terhadap realisasi dan jumlah pagu anggaran, Revisi anggaran dalam rangka penghematan anggaran untuk menghadapi pandemi Covid-19 dilakukan dengan melakukan pengurangan anggaran yang bersumber dari akun yang dianggap tidak prioritas. Penyajian terhadap akun khusus penanganan Covid-19 di laporan keuangan tidak memiliki segmen khusus, disajikan sebagai belanja barang pada laporan realisasi anggaran dan disajikan sebagai beban barang dan jasa pada laporan operasional